MODERNIZATION OF GELMINT PROFILING AND MEASURES AGAINST THE EPIDEMIC IN ALL RESIDENTIAL REGIONS OF THE REPUBLIC UZBEKISTAN - Nomozboyeva Maftuna Abduhamid kizi; Normurodova Hulkaroy Furkatjonovna; Abdurahmonova Dilnoza Komil qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
ABSTRACT: In this article, the modern preventive measures of the Republic of Uzbekistan for the widespread spread of helminths among all the population and for the suffering residents, as well as the efforts aimed at preventing the modern epidemic of helminths, are widely covered.